MATLAB-SIMULINK BASED INFORMATION SUPPORT FOR DIGITAL OVERCURRENT PROTECTION TEST SETS - I. V. Novash; F. A. Romaniuk; Yu. V. Rumiantsev; V. Yu. Rumiantsev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The implementation of information support for PC-based and hardware-software based sets for digital overcurrent protection devices and their models testing using MatLab-Simulink environment is considered. It is demonstrated that the mathematical modeling of a part of the power system – viz. of the generalized electric power object – could be based on rigid and flexible models. Rigid models implemented on the basis of mathematical description of electrical and magnetic circuits of a power system can be considered as a reference model for the simulation results that have been obtained with the aid of another simulation system to be compared with. It is proposed to implement flexible models for generalized electric power object in the MatLabSimulink environment that includes the SimPowerSystems component library targeted to power system modeling. The features of the parameters calculation of the SimPowerSystems component library blocks that the power system model is formed of are considered. Out of the Simulink standard blocks the models of a wye-connected current transformers were composed as well as the digital overcurrent protection, missing in the component library. A comparison of simulation results of one and the same generalized electric power object implemented in various PC-based software packages was undertaken. The divergence of simulation results did not exceed 3 %; the latter allows us to recommend the MatLab-Simulink environment for information support creation for hardware-software based sets for digital overcurrent protection devices testing. The structure of the hardware-software based set for digital overcurrent protection device testing using the Omicron CMC 356 has been suggested. Time to trip comparison between the real digital protection device МР 801 and the model with the parameters which are exactly match the parameters of the prototype device was carried out using the identical test inputs. The results of the tests demonstrated a close coincidence of results (the divergence of not more than 8 %), that confirms the possibility of using the suggested hardware-software based test set during the development and debugging of new digital relay protection devices.